Assessment of Peroxide in Saliva During and After At-home Bleaching With 10% Carbamide and Hydrogen Peroxide Gels: A Clinical Crossover Trial - Mailart, M. C. [UNESP]; Sakassegawa, P. A. [UNESP]; Torres, C. R. G. [UNESP]; Palo, R. M. [UNESP]; Borges, A. B. [UNESP] (Operative Dentistry Inc, 2020)
Objectives: This study evaluated the presence of peroxide in saliva using at-home bleaching systems containing hydrogen peroxide (HP) and carbamide peroxide (CP) with a prefilled tray (PT) or conventional tray (CT). Methods and Materials: Participants received bleaching treatments after the sequence randomization (n=10): PT-HP/Opalescence-Go10%; CT-HP/WhiteClass10%; and CT-CP/OpalescencePF10%. Saliva was collected at the following times: baseline; at 1, 5, 15, and 30 minutes after administration; and at 3, 5, and 8 minutes after the tray was removed. Colorimetric analysis using analytic spectrophotometry was performed. The salivary flow (SF) was monitored during use of trays. Data about peroxide concentration (PC) were submitted to repeated-measures analysis of variance and Tukey tests (5%), and toxic dose was calculated based on body weight. The relation between SF and PC was verified with the Pearson correlation test. Results: There was a significant difference for bleaching (p=0.0001) and time (p=0.0003) but not for interaction (p=0.3121). PC was lower for CT-CP in relation to PT-HP and CT-HP. After tray removal, expectoration, of the remaining gel, and mouth rinsing, no peroxide was detected in saliva. Correlation between SF and PC was considered weak (r=0.3379). The overall mean SF was 50.44% during tray use. In general, PC in saliva was 68.72% lower than the estimated toxic dose (0.26 mg/kg/day) considering all the bleaching systems. Conclusions: Higher peroxide levels were detected in saliva with 10% HP gels. Nevertheless, they were below estimated toxic dose and were considered safe in relation to toxicity.